Coronary Heart Disease: Impact of Socioeconomic Status on Unstable Angina/NSTEMI among Population of Karachi - Alam, Shazia; Naqvi, Syed Baqir S; Aslam, Muhammad (Bangladesh Journal of Medical Science, 2016)
Background: In health care system, socioeconomic discrepancy is considered as one of the important factor particularly in case of coronary heart disease, which is substantially higher in lower status individuals described by education, employment position or earnings. Objective: The aim of this study was to analyze the association of socioeconomic impact on unstable angina (UA)/Non-ST elevated myocardial infarction (NSTEMI) among population of Karachi, the largest city of Pakistan. Methods: A prospective survey was conducted in the government and private hospitals of Karachi. Overall 487 hospitalized patients of unstable angina/NSTEMI were included during the study period of 2013-2014. Information on SES was collected through well-structured questionnaires. The statistical analysis was carried out using SPSS version 20.0. Results: Educational level and income seemed to be the most important measures of socioeconomic indicators in relation to the coronary artery disease in the study population. People with lower socioeconomic status had higher levels of unstable angina/NSTEMI admissions and re-hospitalization. The association between socioeconomic status and UA/NSTEMI was more consistent among both genders. Conclusion: Socioeconomic inequalities were more in communities; whose living standard comes under lower economic categories in association of less educational status. Lower SES found strong contribution in hospitalized patients with unstable angina/NSTEMI. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.343-346